Monitoramento e avaliação do Plano Plurianual (PPA) e do orçamento no governo do estado de Sergipe: desafios para a transparência. - Andrade, Ciro Brasil de (2016)
The Multiyear Plan, the Budgetary Guidelines Law and the Annual Budget are the foundation of state planning in Brazil. Access to data and information to accompany the implementation of public policies envisaged in them is a citizen's right, which is not always respected. This work is a qualitative case study, whose objective is to investigate whether the Monitoring and Evaluation (M & E) instruments of budgetary planning (Multiyear Plan, Budgetary Guidelines Law and Annual Budget), adopted by the Government of the State of Sergipe, are accessible and useful so that the citizen can follow the implementation of government programs and actions - thus meeting the transparency requirements of the Law on Access to Information (LAI). The work was developed through bibliographical research, documentary and interviews with key actors in the planning process, using Bardin content analysis for data treatment. The theoretical framework discussed the issue of transparency, information asymmetry - with emphasis on Agency Theory - and monitoring and evaluation concepts in the context of public policies. The conclusion is that the M & E instruments of budget planning are still incipient, hermetic and not very accessible, with a predominance of a financial and fiscal bias. Thus, it does not fully meet LAI's transparency requirements. It was also evident that M & E and transparency practices are hampered by the low degree of consolidation of the institutional planning arrangement in the State Government. At the end, some proposals are presented for the greater effectiveness of these practices within the scope of governmental planning.